KONFLIK ELIT POLITIK DALAM PEMILIHAN UMUM GUBERNUR DAN WAKIL GUBERNUR PROVINSI MALUKU UTARA TAHUN 2007 - Husen, M. Rahmi (Universitas Sam Ratulangi, 2016)
Regional Head Election conflict (Pemiulkada) Governor and Vice Governor of North Maluku province in 2007 involving these time supporters spotted from the rivalry between the pair of Abdul Gafur-Abdurrahim Fabanyo with Thaib Armayin-Gani Kasuba contested the Governor and Vice Governor of North Maluku Province. The conflict took place due to the interests of the two camps to lead North Maluku. This research aims at describing the conflict's political elite in the general election the Governor and Vice Governor of North Maluku province in 2007. The method of research used the qualitative method. Data was collected through in-depth interviews, direct observation, and study the documentation. Sample determined in purposive for in-depth interviews conducted in purposive sampling a number of 15 people consisting of: KPUD provinces and Districts: 2 persons, members of DPRD the North Maluku Provincial/party Poles: 2 persons, community leaders: 1 person, the Candidate Governor and Vice Governor: 2 persons, successful teams: 3 persons, academics: 2 persons, reporters: 2 persons, and NGO Activists: 1 person. Data analysis is carried out, which further descriptive data of the organized were investigated thoroughly and return data that has been collected from various sources. The data collected is then read back overall and made notes about edge data considered important and in line with the focus and purpose of the study, then do the coding of data, easily searched for and found when needed in making the categorization. The next step is done categorization, where the data had meaning the same category made its own name / its own label also earmarked for discover patterns and theme, researchers conducted before of interpretation of data. The final phase done researchers namely interpret research conducted exists for withdrawal conclusion after verifying all the data to answer problems in this election. The research results show that in the implementation of the general election governor and the vice governor of North Maluku 2007 found: First, conflict start seen since stage registration candidates, in which couples H. Mudaffar Syah-H. Rusdi Hanafi cancelled of his preferred candidate by KPUD provincial North Maluku because they did not fulfill regulation the 15 % to the votes and support seats. Second, stage campaign period, conflict can also be seen start hardened because third candidate couple and team the success of protest against the schedule some of which day has fallen during Ramadan and Eid, and when socialization stage the schedule is accepted all parties well. Third, calculation stage and recapitulation the ballot, where conflict is more open and prolonged caused the political elite prefer the interests of each as to be almost no space negotiations to conflict resolution. Fourth, stage conflict resolution, done through state apparatus with the approach security, negotiations, and dialogue. Although recognized, during conflict the political elite never want to sit with to dialogue in order to find resolution (handling) the conflict. Conflict elite politic in general election governor and the vice governor of North Maluku in 2007 it ended after the issuance of the decisions law for the winner by the Supreme Court (MA) and Rejected Dispute Authority Between Agencies (SKLN) requested by KPUD provincial North Maluku in the constitutional court (MK). Suggested, First, the elites politic and the public to the fore must maintain the climate that conducive, far from the nature of brutal and violence and will lead to physical conflict. Second, the elite standing general election to be ready kala and ready to have a real seikap fighter, ready to accept reality political. And when important is the elite party supporters successful the team / supporters, security officials insurer general election to be neutral and uphold rules and regulations. And a third of the political elite must be more oriented in the citizens needs and indicated democratic behavior according to ethics political. Keyword : political elite, conflict, electionRegional Head Election conflict (Pemiulkada) Governor and Vice Governor of North Maluku province in 2007 involving these time supporters spotted from the rivalry between the pair of Abdul Gafur-Abdurrahim Fabanyo with Thaib Armayin-Gani Kasuba contested the Governor and Vice Governor of North Maluku Province. The conflict took place due to the interests of the two camps to lead North Maluku. This research aims at describing the conflict's political elite in the general election the Governor and Vice Governor of North Maluku province in 2007. The method of research used the qualitative method. Data was collected through in-depth interviews, direct observation, and study the documentation. Sample determined in purposive for in-depth interviews conducted in purposive sampling a number of 15 people consisting of: KPUD provinces and Districts: 2 persons, members of DPRD the North Maluku Provincial/party Poles: 2 persons, community leaders: 1 person, the Candidate Governor and Vice Governor: 2 persons, successful teams: 3 persons, academics: 2 persons, reporters: 2 persons, and NGO Activists: 1 person. Data analysis is carried out, which further descriptive data of the organized were investigated thoroughly and return data that has been collected from various sources. The data collected is then read back overall and made notes about edge data considered important and in line with the focus and purpose of the study, then do the coding of data, easily searched for and found when needed in making the categorization. The next step is done categorization, where the data had meaning the same category made its own name / its own label also earmarked for discover patterns and theme, researchers conducted before of interpretation of data. The final phase done researchers namely interpret research conducted exists for withdrawal conclusion after verifying all the data to answer problems in this election. The research results show that in the implementation of the general election governor and the vice governor of North Maluku 2007 found: First, conflict start seen since stage registration candidates, in which couples H. Mudaffar Syah-H. Rusdi Hanafi cancelled of his preferred candidate by KPUD provincial North Maluku